A Thermodynamic Study of Adsorption of Sulfadiazine on Tween 20 and Tween 40 - Ø¹Ù…Ø±Ø§Ù† ÙƒØ§Ø¸Ù…Ø£.Ù…. Ø¯ Ù…ÙˆØ³Ù‰; Ø±Ø´ÙŠØ¯ØØ³ÙŠÙ† Ø¹Ù„ÙŠ (Al-Qadisiyah Journal of Pure Science, 2017)
This study is concerned with Thermodynamic adsorption of antibiotic (Sulfadiazine) on Tween 20 & Tween 40 surfaces. Due to the high usage of Pharmacuticals and Personal Care Products (PPCP) by human, that might led to increase the rate of water pollution specially where no effective ways for treating sewerage waters. Uv-Visible Spectrophotometric technique has been used to study the adsorption isotherms. The results obtained show that adsorption isotherms on the two surfaces were of types S2 and S3 according to Giles classification which agrees with Freundlich equation of adsorption. the isotherms refers to increasing of initial adsorbate concentration substances leads to increasing of adsorption. The study is focused on the effect of temperature between the range of (303-318)K on the adsorption of sulfadiazine and the two surfaces. The results showed that the adsorption of sulfadiazine on Tween20 & Tween40 increase with increase temperature.The effect of acidic function was conducted as well,and the results of adsorption were following: pH= 9.5 Ëƒ 7 Ëƒ 4.5 Î”H values showing adsorption is physical.